Multivariate Synergistic Flexible Metal‐Organic Frameworks with Superproton Conductivity for Direct Methanol Fuel Cells. Issue 51 (8th November 2021) - Li, Zhen‐Hua; Zeng, Hui; Zeng, Guang; Ru, Chunyu; Li, Guanghua; Yan, Wenfu; Shi, Zhan; Feng, Shouhua
Abstract: Improving proton conductivity and fabricating viable metal‐organic frameworks (MOFs) based proton exchange membranes (PEMs) are central issues exploiting electrolyte MOFs. We aim to design multivariate flexibility synergistic strategy to achieve Flexible MOFs (FMOFs) with high conductivity at a wide range of humidity. In situ powder X‐ray diffraction (PXRD) and temperature‐dependent Fourier transform infrared spectra (FT‐IR) prove the synergistic self‐adaption between dynamic torsion of alkyl sulfonic acid and dynamic breathing of FMOF, forming a continuous hydrogen‐bonding networks to maintain high conductivity. Based on the convincing proton conductivity, we construct a series of long‐term durable MOF‐based PEMs that serve as a bridge between MOF and fuel cell. Consequently, the membrane electrode assembly (MEA) of the flexible PMNS1‐40 exhibits a maximum single‐cell power density of 34.76 mW cm −2 and hopefully opens doors to evaluate the practical application of proton‐conducting MOFs in direct methanol fuel cells. Abstract : Multivariate flexible MOF facilitates efficient hydrogen‐bonding formation by synergistic self‐adapting its flexible structure, maintaining excellent proton conductivity. Based on compelling proton conductivity, a single‐cell of MOF‐based PEMs with long‐term durability is assembled and exhibits excellent power density, which is promising for the practical application of proton‐conducting MOFs in DMFCs.